Anterior segment optical coherence tomography of acute primary angle closure - Zhang, Hai Tao; Xu, Liang; Cao, Wei Fang; Wang, Ya Xing; Jonas, Jost B. (Graefe's archive for clinical and experimental ophthalmology, 2010)
To assess anterior segment optical coherence tomographic measurements of patients after acute unilateral primary angle closure (APAC) compared with those of normal subjects.